2015
DOI: 10.1002/jee.20073
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Students' Epistemological Views on Mathematical Methods in Engineering

Abstract: Background This study was motivated by the ubiquity and apparent usefulness of general

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…For example, undergraduate students believe in the certainty of knowledge and its acquisition from authority figures, while graduate students focus on the disorder and uncertainty of knowledge (Jehng, Johnson, & Anderson, ). While some authors describe development of epistemic beliefs as occurring through a series of developmental stages, a view of these beliefs as depending on the domain or even stage of problem solving has recently been described (for a review, see Gainsburg, ). Nevertheless, it has been shown that as students progress through their education, they can develop more sophisticated ideas about engineering problem solving (Choi et al, ; Douglas et al, ; Marra & Palmer, ; Mena, Zappe, & Litzinger, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, undergraduate students believe in the certainty of knowledge and its acquisition from authority figures, while graduate students focus on the disorder and uncertainty of knowledge (Jehng, Johnson, & Anderson, ). While some authors describe development of epistemic beliefs as occurring through a series of developmental stages, a view of these beliefs as depending on the domain or even stage of problem solving has recently been described (for a review, see Gainsburg, ). Nevertheless, it has been shown that as students progress through their education, they can develop more sophisticated ideas about engineering problem solving (Choi et al, ; Douglas et al, ; Marra & Palmer, ; Mena, Zappe, & Litzinger, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This would speak for a need of mathematical knowledge oriented towards the conceptual as well as generic skills such as analytical thinking and problem solving often expected to be implicit in mathematical work (cf. Gainsburg, 2015). This is also reflected in more recent policy documents on engineering curricula (Alpers, 2013a(Alpers, , 2013b.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 86%
“…However, after being exposed to more applied and practice oriented subjects and projects later in their studies, a more engineering oriented view on the way mathematical concepts and methods enter into these activities may develop (cf. Gainsburg, 2015;Kashefi et al, 2013). The result that in both countries performance of the conceptually oriented mathematics is higher for the senior students than for the junior students (Table 2), as well as the appreciation of its role outside the mathematics studies (Figure 4) and for engineering studies in general (Figure 5), is an indication of such development.…”
Section: Observed Patterns In the Datamentioning
confidence: 99%
“…They conducted a study comparing the design process activity of engineering students and expert engineers in which the participants designed a solution to a design problem in a laboratory-based setting [22,23]. This kind of problem is an ill-structured problem because there is no single correct solution, only solutions that better meet the constraints and preferences of the problem statement.…”
Section: Well-structured Versus Ill-structured Problemsmentioning
confidence: 99%
“…Moreover, Atman et al stated that engineering students and expert engineers have to iterate through different stages rather than following a linear process to handle the ill-structured nature of design problems. Many other researchers have also conducted studies in engineering design identifying design problems as ill-structured that require judgements about the solution and high metacognitive skills [23,24,25]. In general, engineering problems are frequently identified as analytical problems (well-structured) or design problems (ill-structured), with the former being highly structured and amenable to algorithmic solutions and the latter requiring nonlinear and iterative solutions [26,27,28].…”
Section: Well-structured Versus Ill-structured Problemsmentioning
confidence: 99%